Effect of crude protein levels and organic selenium supplementation in the diets fed during the breeding season on reproductive parameters of red-winged tinamous (Rhynchotus rufescens) - Felipe, L. [UNESP]; Santos, E. C.; Tavian, A. F.; Góes, P. A. A.; Moraes, V. M. B. [UNESP]; Tonhati, Humberto [UNESP]; Boleli, I. C. [UNESP]; Malheiros, E. B. [UNESP]; Barnabé, V. H.; Queiroz, S. A. [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2010)
There is little information on the nutrition of red-winged tinamous (Rhynchotus rufescens) reared in captivity, and their nutritional requirements still need to be determined. This study aimed at determining dietary crude protein requirements and testing four organic selenium supplementation levels in the diet of red-winged tinamous during the breeding season. Birds were housed in a conventional broiler house divided in 16 boxes with one male and three females each. Iso-energy (2800kcal ME/kg) pelleted feeds, based on corn and soybean meal, were supplied in tube feeders. In the first experiment, treatments consisted of four different diets containing different crude protein (CP) contents (15, 18, 21, or 24%) and in the second experiment, the four diets contained equal protein level (22.5%) and four different organic selenium levels (0, 0.2, 0.4, or 0.8ppm). Data were analyzed by the least square method. The best egg weight and eggshell thickness were obtained with 22.5% dietary CP. Organic selenium did not influence the studied reproductive traits of red-winged tinamous (Rhynchotus rufescens) males or females.
Keywords: Egg weight; Fertility; Nutrition; semen quality; shell thickness